Autonomy and Dependence of International Cooperative Ventures: An Exploration of the Strategic Performance of U.S. Ventures in Mexico - ROBINS, James Arthur (Institutional Knowledge at Singapore Management University, 2002)
Researchers have begun to view international cooperative ventures as complex, multiparty organizations in which foreign and local firms and the venture itself all have distinct roles. This approach has important implications for the venture strategies of foreign firms in emerging economies. This study explores relationships between the resource contributions of parent firms and US managers' assessment of venture performance in a sample of established US-Mexican ventures. The research suggests that mature cooperative ventures are expected to achieve autonomy from parent firms in key areas at the same time that certain forms of strategic dependency also are important to success.